An innovative safety format for structural system robustness checking - Tur, Andrei; Tur, Viktar; Derechennik, Stanislav; Lizahub, Aliaksandr (Budownictwo i Architektura / Civil and Architectural Engineering, 2020)
The estimation of structural robustness remains one of the most important stages of the design of structural systems. Recommended design strategies for the robustness assessment are based on the provisions specified in the actual EN 1991-1-7 and ISO 2394:2015. Currently, the EN 1991-1-7 and ISO2394:2015 allows the use of indirect tie-force method, but normally, non-linear pseudo-static analysis is widely used, because it is based on more realistic constitutive relations for basic variables, which enables a simulation of the real structural behaviour. Implementation of the non-linear pseudo-static analysis for the assessment of a structural system in accidental design situations requires to adopt a different approach to safety format. The paper presents an innovative approach to safety format calibration for non-linear analysis of RC-structures subjected to accidental loads. The proposed method of the robustness estimation is based on the joint energy-saving (conversion) approach and the full probabilistic method for the estimation of a safety format for pseudo-static non-linear response of modified (damaged) structural system. The proposed probabilistic considerations are based on the Order Statistic Theory.